Pengelolaan Pantai Marina Boom Banyuwangi Berbasis Masyarakat - Ihyatur Rahma Melinda; Sri Murtini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Marina Boom Beach in Banyuwangi has developed into a modern tourist destination, with the number of visitors increasing by 40% in the last three years. However, this rapid development has caused problems such as damage to the mangrove ecosystem and inequality of community members' participation in local management. This study aims to analyze the dynamics of community participation in the management of Marina Boom Beach and identify obstacles that hinder the participation of marginal groups (youths and women). This study uses qualitative research methods with the design of phenomenological case studies. Data collection is done through participant observation, in-depth interviews with key informants (managers, government officials, and community leaders), and library reviews. Data analysis interprets the informant's field experience using the Miles and Herberman interaction model. Research results show that public participation in the management of Marina Boom Beach is not comprehensive. The role of environmental conservation is still dominated by elderly fishermen centered around the "Laskar Marina" group, while the participation of youth and women is still sporadic and minimal. Major obstacles include a lack of reproduction of roles and limited opportunities for local people to participate in the policy-making process. This study concluded that a more integrated community-based management model was needed to harmonize the economic benefits of tourism, ecological sustainability, and social justice in coastal communities.